2015
DOI: 10.7763/ijesd.2015.v6.685
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Drinking Water from Water Dispenser Machines

Abstract: The aim of this study was to investigate the microbial quality of drinking water distributed through water dispenser machines located in schools and universities in Ajman, UAE. In total, 49 drinking water samples were collected from water dispenser machines in the schools and university's premises in the emirate of Ajman. Total coliform and E.coli were detected using Colilert test. P. aeruginosa colonies were counted on Pseudomonas agar using the membrane filtration method. Overall, 25 out of total 49 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…However, reported by Aruna & Camoens [13], precautions have to be taken by the consumers when using this vending machine water as six out of 14 samples randomly picked from several places in Kuala Lumpur were found to have either coliform or E.coli and did not contain free chlorine for disinfection purpose. The similar cases were also reported in Los Angelas [14] and Dubai [15]. All incidents were concluded to be related to the poor maintenance and improper hygienic conditions of water vending machine.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, reported by Aruna & Camoens [13], precautions have to be taken by the consumers when using this vending machine water as six out of 14 samples randomly picked from several places in Kuala Lumpur were found to have either coliform or E.coli and did not contain free chlorine for disinfection purpose. The similar cases were also reported in Los Angelas [14] and Dubai [15]. All incidents were concluded to be related to the poor maintenance and improper hygienic conditions of water vending machine.…”
Section: Introductionsupporting
confidence: 75%
“…Coliforms and E.coli presence and absence tests were performed using colilert powder indicated negative results when none of the vended sample water showing any colors of fluorescence. This result indicates that the vended water quality in Parit Raja area are still safe to be consumed in terms of total coliform presence as 6 samples over 49 samples were detected to contain total group members in dispenser machines in Ajman, UAE [15]. Similar observation was also revealed the presence of total coliforms in 13 samples out of 40 drinking water vending machines in Los Angeles due improper scheduled maintenance [14].…”
Section: Resultsmentioning
confidence: 58%
“…Hygiene and the maintenance of water integrity for consumption avoid contamination. Moosa et al (2015) evaluated water quality in drinking troughs in schools and at the university in Ajman, United Arab Emirates, and detected Pseudomonas aureginosas, total coliforms and E. coli: 32.65% of the 49 samples assessed were contaminated by total coliforms and unfeasible for consumption according to the legislation of the country mentioned above. The authors reported that the drinking water should not contain the bacterium.…”
Section: Microbiological Assessmentmentioning
confidence: 99%
“…The availability of safe drinking water therefore represents a global challenge. Although the authorities have sustained substantial efforts in two priority areas: water quantity and water quality assurance [3,4]. UNCHR 2 et al [2] highlight that water is a very important resource needed to sustain life, and safe drinking water is a fundamental requirement for human life.…”
Section: Introductionmentioning
confidence: 99%